Network-based machine learning in colorectal and bladder organoid models predicts anti-cancer drug efficacy in patients - JungHo Kong (Nature Portfolio, 2020)
Cancer patient classification using predictive biomarkers for anti-cancer drug responses is essential for improving therapeutic outcomes. Here, the authors present a machine-learning framework to identify robust drug biomarkers by taking advantage of network-based analyses using pharmacogenomic data.